2017
DOI: 10.3389/fphys.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hemodynamic Load in Early Embryonic Stages Alters Endocardial to Mesenchymal Transition

Abstract: Normal blood flow is essential for proper heart formation during embryonic development, as abnormal hemodynamic load (blood pressure and shear stress) results in cardiac defects seen in congenital heart disease. However, the progressive detrimental remodeling processes that relate altered blood flow to cardiac defects remain unclear. Endothelial–mesenchymal cell transition is one of the many complex developmental events involved in transforming the early embryonic outflow tract into the aorta, pulmonary trunk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 95 publications
0
46
0
Order By: Relevance
“…As stated earlier, several studies have reported the fact that perturbation of hemodynamics in the embryonic heart leads to a spectrum of congenital heart / valve defects (Hu and Clark, 1989; Hogers et al, 1997; Hogers et al, 1999; Reckova et al, 2003; Stekelenburg-de et al, 2003; Lucitti et al, 2005; Menon et al, 2015; Ford et al, 2017; Midgett et al, 2017). We recently showed that altering intracardiac hemodynamics by partial OFT constriction via banding, has consequences at the cellular and genetic level (Menon et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As stated earlier, several studies have reported the fact that perturbation of hemodynamics in the embryonic heart leads to a spectrum of congenital heart / valve defects (Hu and Clark, 1989; Hogers et al, 1997; Hogers et al, 1999; Reckova et al, 2003; Stekelenburg-de et al, 2003; Lucitti et al, 2005; Menon et al, 2015; Ford et al, 2017; Midgett et al, 2017). We recently showed that altering intracardiac hemodynamics by partial OFT constriction via banding, has consequences at the cellular and genetic level (Menon et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…This fact is well documented by numerous studies, which demonstrate that altering hemodynamics through the developing heart, leads to a spectrum of congenital heart defects (Hu and Clark, 1989; Hogers et al, 1997; Hogers et al, 1999; Hove et al, 2003; Reckova et al, 2003; Stekelenburg-de et al, 2003; Lucitti et al, 2005; Menon et al, 2015; Ford et al, 2017; Midgett et al, 2017). Our laboratory recently reported on the genetic / cellular consequences of altering hemodynamics by increasing shear stress by banding in the embryonic chick heart (Menon et al, 2015); adding to the growing body of research that emphasizes the importance of maintaining normal hemodynamics during development.…”
Section: Introductionmentioning
confidence: 83%
“…Further increases in contractility and WSS led to valve leaflet hyperplasia, in part mediated by increased endocardial differentiation into valve-forming cells via EndoMT ( Figure 6). Rugonyi et al showed that cardiac contractility and hemodynamic load increase EndoMT in the OFT of developing chick embryos (33). Butcher and Merryman et al further demonstrated shear stress-and myocardial contractility-mediated EndoMT in vitro (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Midgett et al. also found that altered hemodynamics leads to changes in the myofibrils and reorganization of mitochondria in the cardiac outflow tract of chicken embryos . Rogers et al used a biomimetic cardiac tissue model to adapt hiPSC‐derived CMs to physiological hemodynamic loads.…”
Section: Remaining Challenges Of Using Pscs For MI Therapymentioning
confidence: 99%